Models for Integration of Flexibility Sources in Regional Electricity Markets - Krstevski, Petar; Mateska, Aleksandra Krkoleva; Borozan, Stefan (IEEE, 2022)
This paper addresses the issue of participation and integration of various providers of flexibility, such as generation from renewable energy sources (RES), demand side management (DSM), and electricity storage systems (STO), into electricity markets. For this purpose, the paper presents business models for participation of flexibility providers in the existing electricity day-ahead (DAM), intraday markets (IDM) and electricity balancing markets. In addition, the provision of new services to the system operators through concepts of local flexibility markets, congestion management markets as well as other ancillary services, is investigated.
Keywords: Flexibility , RES , Energy Storage , Demand Side Management , Congestion Management Markets , Network Services